Analisis Media Flashcard Berbasis Augmented Reality (AR) terhadap Kemampuan Numerasi Siswa Kelas III SD 41 Ampenan - Alfina; Elza Maulia Sopani; Kadek Listya Widyastuti; Ulya Sulistina; Muhammad Isra; Siti Istiningsih (Action Research Journal, 2026)
This study aims to analyze the application of Augmented Reality (AR)-based flashcards in improving the numeracy skills of elementary school students. The approach used is qualitative phenomenology with an Ex Post Facto design,involving teachers and students of grade III of SD Negeri 41 Ampenan as the subjects of the study. Data was collected through in-depth interviews, observations, and documentation of learning outcomes, then analyzed using data reduction techniques and descriptive tests on the collected data. The results of the study show that the application of AR-based flashcard media significantly improves students' understanding of the shapes and properties off at shapes, while also developing contextual numeracy skills.From the perspective of learning technology, particularly in terms of design, development, utilization, and management, this media is considered valid, practical, and effective in creating an interactive and meaningful mathematics learning process that is in line with contextual numeracy skills. From the perspective of learning technology, particularly in terms of Design, Development, Utilization, and Management, this media is considered valid, practical, and effective in creating an interactive and meaningful mathematics learning processthat is in line with the cognitive characteristics of students at the concrete operational stage. The responses of teachers and students showed an increase in motivation, participation, and enthusiasm for learning. Thus, AR-based flashcard media is a relevant pedagogical innovation in transforming learning from abstract concepts into concrete, contextual, and locally-based learning experiences, while strengthening numeracy in elementary schools